EXPLORING DEVELOPMENT STAGES OF INTERCULTURAL FRIENDSHIP AMONG EFL LEARNERS - Khairatunnisa, Khairatunnisa; Muhamad, Malisa; Susanti, Ani (Universitas Islam Sumatera Utara (UISU), 2022)
Intercultural communication or Intercultural Communicative Competence (ICC) is the different condition of society that used symbol systems and rules for communication and interaction with other cultures and languages. This research explored the stages of the intercultural friendship of English Foreign Language (EFL) students in Indonesia who joined the International Community Service. Nine students in the same events participated in collecting the data of the questionnaire and interview based on the three familiar theories: trial, enmeshment, and renegotiation. Then the results showed that the students had prepared information about the place of events and learned the new cultures and habits of the different societies. The other one, the students avoided sensitive issues such as ethnicity, religion, and race to accept the contradiction among the students and society to understand one another to evaluate the contradiction to be a positive value based on the three theories of intercultural friendship. Lastly, their challenges were between them and society, and the students and their friends in a small group. Diversification of purpose and goal of their project made them difficult to implement such as internet connection and public fasilities. Besides, the village situation was poorer than other communities were, and required some facilities to assist them in their everyday operations. In accordance with the results, keeping good communication and relationship would be easier for students or institutions for the next event. The program was continued for the other participants to make the successful goals.